Perangkap Feromon Seks untuk Penggerek Batang Padi Kuning Scirpophaga incertulas - Hendarsih S.; N. Usyati (Universitas Gadjah Mada, 1999)
An experiment was done to test the color, size, structure, dispenser cover, surfactant, and duration of observation of the sex pheromone trap for the yellow rice stem borer (YRSB) Scirpophaga incertulas Wlk. Each trap was equipped with an attractant for the male moth of YRSB in a rubber septa dispenser containing 1 mg of synthetic female YRSB sex pheromone 3(Z9-16:Ald) + (Z11-16:Ald) (Cork, NRI, UK). All tests were done in RCBD with replications. Difference among treatments were evaluated by DMRT. Data revealed that yellow colored trap was the most attractive for the YRSB folowed by the white ones. Cylindrical trap with the diameter of 25 and 55 cm caught more moths compared to 15 cm and 35 cm, although it was not different from the 25 x 25 cm box trap. The design of dispenser cover could be either rectangular or rounded in 20 cm size. The surfactant for the trap could be lubricating oil, vegetable oil or detergent. The number of moths were observed daily. Twice and once a week observations did not differ significantly.